Normal T-cell activation in elite controllers with preserved CD4+ T-cell counts. (November 2015) - Bansal, Anju; Sterrett, Sarah; Erdmann, Nathan; Westfall, Andrew O.; Dionne-Odom, Jodie; Overton, Edgar T.; Goepfert, Paul A.
Abstract : Background: HIV elite controllers suppress HIV viremia without antiretroviral therapy (ART), yet previous studies demonstrated that elite controllers maintain an activated T-cell phenotype. Chronic immune activation has detrimental consequences and thus ART has been advocated for all elite controllers. However, elite controllers are not a clinically homogenous group. Since CD4% is among the best predictors of AIDS-related events, in the current study, we assessed whether this marker can be used to stratify elite controllers needing ART. Methods: Sixteen elite controllers were divided into two groups based on CD4% (EC hi > 40% and EC lo ⩽40%), and T-cell subsets were analyzed for markers of memory/differentiation (CD45RA, CCR7, CD28), activation (CD38/HLA-DR), immunosenescence (CD57), costimulation (CD73, CD28) and exhaustion (PD-1, CD160, Tim-3). Monocyte subsets (CD14, CD16) were also analyzed and sCD14 levels were quantified using ELISA. Results: In the EC hi group, expression of activation, exhaustion, and immunosensescence markers on T cells were significantly reduced compared with the EC lo group and similar to the seronegative controls. The EC hi group expressed higher levels of costimulatory molecules CD28 and CD73 and had lower levels of monocyte activation (HLA-DR expression) with a reduced frequency of inflammatory monocyte (CD14 ++ CD16 + ) subset. Furthermore, the EC hi group maintained a stable CD4% during a median follow-up of 6 years. Conclusion: Elite controllers with preserved CD4 + T cells (EC hi ) have normal T-cell and monocyte phenotypes and therefore may have limited benefit from ART. CD4% can be an important marker for evaluating future studies aimed at determining the need for ART in this group of individuals. Abstract : Supplemental Digital Content is available in the text